A CRITICAL DISCOURSE ANALYSIS OF RHETORICAL DEVICES IN JOE BIDEN INAUGURATION SPEECH 2021 - Umam, Ittihadul; Laili, Elisa Nurul (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
Abstract: In this study, researchers used a descriptive qualitative method to analyze data on rhetorical devices and how this was applied in the inauguration speech for the 2021 United States president. This study used theory from Jones and Peccei (2004) and the CDA approach by Van Dijk at the microstructural level. This study aims to find out how the speaker conveys the implied meaning by using rhetorical devices and also to find out how this is constructed in this speech. After data collection, the data is identified and analyzed using rhetorical devices based on the theory of Jones and Peccei 2004 coupled with critical discourse analysis which is limited to the microstructural elements of Van Dijk's theory. The researcher found that the speaker used all kinds of rhetorical devices, except for euphemisms. Those rhetorical devices are metaphor, parallelism, the rule of three, and pronouns. There are 16 devices found in the data. Based on the findings, the most dominant is parallelism, this shows that speakers like to use similar structures in explaining and conveying the contents of speech without changing the context. In addition, it can be concluded that the use of rhetorical devices and critical discourse analysis approaches in delivering speeches can contribute to making speeches more interesting and memorable.